OUTCOMES OF ADJUVANT INTRAVESICAL GEMCITABINE THERAPY FOR NON-MUSCLE-INVASIVE BLADDER CANCER AT NGHE AN ONCOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective:To evaluate the clinical characteristics, paraclinical findings, and outcomes of adjuvant intravesical Gemcitabine therapy in patients with non-muscle-invasive bladder cancer (NMIBC) following transurethral resection of bladder tumor (TURBT).Materials and Methods:A retrospective descriptive study was conducted on 37 patients with non-muscle-invasive bladder cancer (Ta, T1, and carcinoma in situ [CIS]) who underwent TURBT followed by intravesical Gemcitabine instillation at Nghe An Oncology Hospital between January 2020 and June 2025.Results:The mean age of the patients was 65 ± 9 years, with males accounting for 89% of the cohort. Gross hematuria was the most common presenting symptom. The overall recurrence rate was 24.3%, including a local recurrence rate of 13.5%. Adverse events associated with intravesical Gemcitabine were generally mild, with bladder irritation being the most frequently reported. No severe complications were observed.Conclusion:Intravesical Gemcitabine is a safe and effective adjuvant treatment for patients with non-muscle-invasive bladder cancer after TURBT, reducing the recurrence rate and prolonging recurrence-free survival.
Keywords: Non-muscle-invasive bladder cancer; intravesical Gemcitabine; recurrence rate.